Odpowiedzi

  • Użytkownik Zadane
2009-12-19T18:08:43+01:00
1 . 3x-1,5 + 2y+6=3,5
3x+2y= 3,5-6+1,5
3x+2y= -1

2. 6x-2+3y+9=-1
6x+3y= -1-9+2
6x+3y= 8
2009-12-19T18:19:15+01:00
3(x-1/2)+2(y+3)=3 1/2
3x-1:3-y+3:2=-1

3x-3/2+2y+6=3 1/2
3x-1:3-y+3:2=-1 / *3

3x-3/2+2y+6=3 1/2
3x-1-(3y+9):2=-3 /*2

3x+2y=3 1/2 -4 1/2
6x-2-3y-9=-6

3x+2y=-1 / *(-2)
6x-3y=5

-6x-4y=2
6x-3y=5

-7y=7 /: (-7)
6x-3y=5

y=-1
6x=2 /: 6

y=-1
x=1/3
2009-12-19T18:22:32+01:00
3(x-0,5)+2(y+3)=3,5
3x-1(dzielone przez 3)-y+3(dzielone na dwa)=-1 |×6

3x-1,5+2y+6=3,5
2(3x-1)-3(y+3)=-1

2y=3,5-3x+1,5
6x-2-3y-9=-1

2y=5-3x /÷2
6x-2-3y-9=-1

y=2,5-1,5x
6x-2-3(2,5-1,5x)-9=-1

y=2,5-1,5x
6x-2-6+4,5x-9=-1

y=2,5-1,5x
6x+4,5x=-1+2+6+9

y=2,5-1,5x
55/10x=16 /×10/55

y=2,5-1,5x
x=160/55

y=2,5-1,5x
x=2 50/55

y=2,5-1,5x
x=2 10/11

y=2 5/10-15/10×160/55
x=2 10/11

y=2 55/110-48/11
x=2 10/11

y=165/110-480/110
x=2 10/11

y=-315/110
x=2 10/11

y=-63/22
x=2 10/11

y=-2 19/22
x=2 10/11

Pozdrawiam ;]